Orofacial Disorders : Current Therapies in Orofacial Pain and Oral Medicine - Ferreira, João N. A. R.; Fricton, James; Rhodus, Nelson (Springer International Publishing : Imprint: Springer, 2017)
This cutting-edge book is a quick reference guide to the evidence-based evaluation, diagnosis, and management of the broad spectrum of orofacial disorders. Each chapter is devoted to a particular disease or disorder and presents advances in understanding of the condition, the most recent evaluation and diagnostic strategies, and up-to-date treatment approaches. In addition, strategies for integration of care into routine dental practice are explained, and information provided on practice management concepts. The coverage encompasses the latest technological advances in the field, such as gene transfer techniques, new pharmaceuticals, innovations in craniofacial imaging, and intelligent digital records for orofacial disorders. Although the management of orofacial disorders is emerging as a distinct field of dentistry, many dentists and physicians are unfamiliar with recent advances in the care of patients with orofacial disorders, orofacial pain, and headache. This book, written by world class experts, is deliberately geared to the level of understanding of a clinician nonscientist. It will serve as an ideal evidence-based reference and source of specific clinical recommendations in daily practice. .